2013
DOI: 10.1890/12-0672.1
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐modeling soil organic carbon sequestration potential and its application at regional scale

Abstract: Upscaling the results from process-based soil-plant models to assess regional soil organic carbon (SOC) change and sequestration potential is a great challenge due to the lack of detailed spatial information, particularly soil properties. Meta-modeling can be used to simplify and summarize process-based models and significantly reduce the demand for input data and thus could be easily applied on regional scales. We used the pre-validated Agricultural Production Systems sIMulator (APSIM) to simulate the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…This result may attribute to the fact that Australian agro‐ecosystems are mainly water‐ rather than temperature‐limited, resulting in the greater response of SOC change to precipitation than to temperature. This result is also consistent with our previous modelling study assessing drivers of SOC change across the Australian cropping regions (Luo et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result may attribute to the fact that Australian agro‐ecosystems are mainly water‐ rather than temperature‐limited, resulting in the greater response of SOC change to precipitation than to temperature. This result is also consistent with our previous modelling study assessing drivers of SOC change across the Australian cropping regions (Luo et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…A great number of observational and modelling studies have acknowledged the general importance of climatic, edaphic and biotic factors in controlling SOC dynamics in different context (Carvalhais et al., ; Luo et al., ; Schimel et al., ; Wynn et al., ). Our results identified that C input amount, total SOC content, and precipitation are the three most important variables controlling SOC dynamics and could explain the majority of the variances in observed SOC change rates for the environments included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results strongly suggest that including soil food web parameters will enhance the predictive capacity of C and N cycling models. Process-based C and N cycling models require detailed input information that is often not available on regional scales (33), and general relationships between soil food web properties and processes of C and N cycling have the potential to simplify these models. Although more validation is needed (for example, within the countries and soil types sampled), the simple relationships between earthworms and CO 2 production or between AMF abundance and N leaching might help parameterize C cycling (34) and ecosystem service models (35).…”
Section: Resultsmentioning
confidence: 99%
“…Primary productivity and SOC decomposition rates are influenced by environmental factors (i.e. initial SOC content, temperature, rainfall) and management practices such as tillage practices, fertilization, and crop rotation systems (Ransom et al, 2011;Luo et al, 2013). These factors, and their resultant influence on SOC, vary spatially (Van Der Hilst et al, 2012).…”
Section: Introductionmentioning
confidence: 99%